A Model of Chinese Spelling Development in Hong Kong Kindergarteners. (March 2022) - Ye, Yanyan; McBride, Catherine; Yin, Li; Cheang, Leo Man-Lit; Tse, Chun Yu
Copying characters presented previously (delayed copying) is an important skill in Chinese literacy acquisition. The relations of delayed copying and a set of literacy-related skills (including vocabulary knowledge, rapid automatized naming, phonological awareness, morphological awareness, and orthographic awareness), visual-orthographic judgment, motor coordination, pure copying of foreign scripts, and delayed copying to Chinese spelling were examined among 294 typically developing Hong Kong kindergarteners. With all other variables statistically controlled, rapid automatized naming, phonological awareness, morphological awareness, orthographic awareness, motor coordination, and delayed copying all uniquely explained Chinese spelling. To further investigate how delayed copying interacts with other skills, path analyses were conducted. The final model showed that vocabulary knowledge, visual-orthographic judgment, and pure copying had indirect effects on spelling through delayed copying. These findings partly support spelling models developed in alphabetic writing systems, but also reflect the uniqueness of Chinese. In addition, results suggest that delayed copying is a unique window into how children learn to write words in Chinese. The potentially critical role of delayed copying in Chinese spelling makes it a potentially good clinical indicator of early spelling proficiency and spelling difficulties.